Analysis of the development and diffusion of technological innovations in oil spill forecasting: The MEDESS-4MS case. (November 2016) - Marcati, Alberto; Prete, M. Irene; Mileti, Antonio; Cortese, Mario; Zodiatis, George; Karaolia, Andria; Gauci, Adam; Drago, Aldo
Abstract: This paper presents a case study on the management of users' engagement in the development of a new technology. Based on the experience of MEDESS-4MS, an integrated operational model for oil spill Decision Support System covering the whole Mediterranean Sea, the case study is aimed at the development of a framework for user engagement and for the management of its dual logic. Indeed, users may play a dual role in the innovation process, contributing to both the design of the innovation and its promotion. Users contribute to shaping the innovation, by aggregating and integrating knowledge, and they facilitate its diffusion, by adopting the innovation and fostering its adoption within the socio-economic system.